2020
DOI: 10.1101/2020.09.30.321331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheGiardia lambliaribosome structure reveals divergence in translation and quality control pathways

Abstract: Giardia lamblia is a human pathogen of worldwide importance with limited treatment options. Its unusual molecular biology presents targets for new therapies and the opportunity to explore the fundamental features of important biological mechanisms. We determined the structure of the G. lamblia 80S ribosome by cryoelectron microscopy, revealing how it combines eukaryotic and bacterial features. The structure reveals regions that are rapidly evolving, including depletion of A and U bases from its rRNA. Specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Saccharomyces cerevisiae ) ( Supplementary Figure S7 ). While working on the current manuscript, an additional structural study of the GL ribosome, at lower resolution, was published by Eiler et al in bioRxiv, which discussed a lower amount of adenines and uridines compared to other species and concluded that all the important eIF3 binding sites are conserved ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Saccharomyces cerevisiae ) ( Supplementary Figure S7 ). While working on the current manuscript, an additional structural study of the GL ribosome, at lower resolution, was published by Eiler et al in bioRxiv, which discussed a lower amount of adenines and uridines compared to other species and concluded that all the important eIF3 binding sites are conserved ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we empirically annotated the 3′ UTRs, for 2630 expressed genes in G. lamblia using a combination of 3′-end short- and long-read sequencing. According to our RNA-seq data ( Eiler et al 2020 ), 6616 of the 9700 predicted coding genes in the genome annotation used for this study are expressed at an FPKM of 10 or higher. This indicates that we have annotated about 40% of the expressed transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…Second, consistent with short UTR regions, the genome of G. lamblia is generally very compact such that only eight genes contain introns and five undergo transsplicing, while the number of protein-coding genes is between 5000 to 9000, depending on genome annotation (Xu, Jex, et al, 2020). Third, G. lamblia has streamlined machinery for transcription (Best, 2004;Morrison et al, 2007), splicing (Iyer et al, 2019;Nixon et al, 2002), and translation (Eiler et al, 2020;L. Li & Wang, 2004), and lacks many protein components that are essential for viability in most other eukaryotes, such as the translation initiation factor eIF4G (L. Li & Wang, 2004;Morrison et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, consistent with short UTR regions, the genome of G. lamblia is generally very compact with only eight genes that contain introns and five that undergo trans-splicing, while the number of protein-coding genes is between 5000 to 9000, depending on genome annotation (Xu, Jex, et al, 2020). Third, G. lamblia has streamlined machinery for transcription (Best, 2004;Morrison et al, 2007), splicing (Iyer et al, 2019;Nixon et al, 2002), and translation (Eiler et al, 2020;L. Li & Wang, 2004), and lacks many protein components that are essential for viability in most other eukaryotes, such as the translation initiation factor eIF4G (L. Li & Wang, 2004).…”
Section: Introductionmentioning
confidence: 99%